TELAAH MUBADALAH DALAM KAJIAN DISPENSASI NIKAH : TELAAH MUBADALAH DALAM KAJIAN DISPENSASI NIKAH - Hermanto, Agus; Fikri, Arif; Santoso, Rudi; Hadaiyatullah, Syeh Sarip (Islamic Civil Law Departement of Shari'a Faculty at Islamic State University of Sultan Maulana Hasanuddin Banten, 2024)
The laws and regulations in Indonesia have regulated the existence of new regulations regarding the age limit for marriage, which is 19 years old for men and women, as stipulated in Law Number 16 of 2019 in response to the birth of the Constitutional Court Decision Number 22/PUUXV/2017, marriage dispensation can be granted if it meets two requirements, namely; First, urgent and have, Second, have sufficient evidence. In fact, this rule often makes it difficult for the community, so that finally many efforts to dispensate marriage are made in order to be able to carry out formal marriage contracts. The problem is how do judges respond to the submission of marriage dispensation to children who are far from the minimum age limit for marriage, which is 19 years for men and women, and what is their contribution to efforts to reform marriage law in Indonesia? To contribute new ideas to the renewal of marriage law scientifically and logically. This research is a type of library research, with a scientific-rational approach to the minimum age limit for marriage in Law Number 16 of 2019, with the theory of sadd al-dzariah as an effort to be able to present legal justice. The conclusion is that the determination of the Religious Court judge regarding marriage dispensation on urgent grounds as the main argument, so that there are often decisions on marriage dispensation at the age of under 16 years, although sadd al-dzariah is a solution that is solutive according to the evidence submitted, but logically it violates the rules of scientific-rational. Keywords: Dispensation, urgent, mubadalah review